2014
DOI: 10.1590/2237-6089-2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and staging of bipolar disorder: a systematic review

Abstract: Introduction: A growing body of evidence suggests that bipolar disorder (BD) is a progressive disease according to clinical, biochemical and neuroimaging findings. This study reviewed the literature on the relationship between specific biomarkers and BD stages. Methods: A comprehensive literature search of MEDLINE and PubMed was conducted to identify studies in English and Portuguese using the keywords biomarker, neurotrophic factors, inflammation, oxidative stress, neuroprogression and staging models cross-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 96 publications
1
24
0
Order By: Relevance
“…Indeed, recent staging models include a high number of recurrences as an indicator of late stage BD (Berk et al, 2007). As suggested by a growing body of evidence, together with a clear understanding of the clinical course of the disease, the identification of biomarkers is fundamental for the development of staging models which may improve treatment guidelines and lead to the development of more efficient, individually tailored treatment regimens (Kapczinski et al, 2014;Roda et al, 2015). If confirmed by further studies, decreased levels of Glucagon and GLP-1 could represent a marker of late-stage patients with BD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent staging models include a high number of recurrences as an indicator of late stage BD (Berk et al, 2007). As suggested by a growing body of evidence, together with a clear understanding of the clinical course of the disease, the identification of biomarkers is fundamental for the development of staging models which may improve treatment guidelines and lead to the development of more efficient, individually tailored treatment regimens (Kapczinski et al, 2014;Roda et al, 2015). If confirmed by further studies, decreased levels of Glucagon and GLP-1 could represent a marker of late-stage patients with BD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cytokines are key signaling molecules that regulate both innate and adaptive immunological responses and have widespread effects on the neuroendocrine system, neurogenesis, neurocircuitry, and neurotransmitter metabolism (Haroon et al, 2012). Therefore, peripheral cytokine fluctuations have been proposed as biomarkers for disease activity, affective state, or the disease nature for BP (Roda et al, 2015). Most studies, however, have a mixed group of BP patients (ie, BP-I patients and BP-II patients) to compare with a control group (Modabbernia et al, 2013; Munkholm et al, 2013a, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, correlating these symptoms with prodromal biomarkers offers an exciting juncture whereby targeted interventions could be opportunistically employed to prevent neurodegenerative changes from accruing as the disease progresses. 11,91 Nevertheless, empirical data supporting the use of biomarkers for outcome prediction in prodromal stages are limited. 92 One of the first studies, conducted by Padmos et al, 93 identified a discriminating and coherent expression of 19 pro-inflammatory genes transcription in monocytes of patients with BD and in the offspring of BD parents.…”
Section: Biomarkersmentioning
confidence: 99%
“…10 Biomarkers seem to play an important role in evaluating disease activity and progression associated with different mood states (mood biomarkers), as well as to identify specific characteristics of the disease (trait biomarkers). 11,12 The available evidence indicates that neurotrophins, oxidative stress, and inflammation are linked to the acute and euthymic phases of BD, 13,14 and indicate the presence of systemic toxicity. 15 The use of clinical staging models is emerging as a novel and useful paradigm to inform diagnosis and treatment of BD.…”
Section: Introductionmentioning
confidence: 99%